Myocardial infarction in normal coronary artery (MINCA): Death in healthy military personnel - Abdul Razak, Nadiawati; Mohd Nor, Faridah; Mohamad Anuar, Nur Najmi; Kamarudin, Ahmad Zakuan (Life Sciences, Medicine and Biomedicine, 2022)
Sudden unexpected death among healthy military personnel leads to a false allegation from family members. However, majority of the deaths were related to an abnormal cardiac condition. Objective: The occurrence of patent coronary vessels in sudden deaths demands histological examination and/or molecular study to detect underlying diseases, which need to be highlighted especially in a centre with limitation of post-mortem computed tomography (PMCT) or virtopsy. In this article, a case of a young healthy male personnel, who died during routine training was reported. He collapsed after a 10-minute jog. An autopsy was performed to determine the cause of death. The autopsy showed a moderately built male. No fatal external injuries were found. Internal examination showed cardiomegaly and patent coronaries. The cardiac markers were markedly raised with normal toxicological analysis. Histology of the heart showed a recent myocardial infarct, hence the cause of death was determined as myocardial infarction in normal coronary artery (MINCA). Conclusion: Annual medical screening is highly recommended to detect any cardiac abnormalities among military personnel. Screening may be extended for a genetic study in suspicious and strong family history to exclude a conduction defect or channelopathy.